International investment instruments : a compendium (UN New YorkUS)
Presents a selection of international instruments relating to foreign investment and the activities of transnational corporations. Consists of legally-binding instruments, mainly multilateral conventions and regional agreements that have entered into force. Includes also, a number of 'soft law' documents, such as guidelines, declarations and resolutions adopted by intergovernmental bodies.
Keywords: INTERNATIONAL INVESTMENT